Соавторы: роман / Александра Маринина - Маринина Александра Борисовна (Эксмо, 2004)
Экземпляры: ф.16 (20241009) / Инвентарный номер: 65282 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: М 26 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.7